Efficacy of early rehabilitation therapy on movement ability of hemiplegic lower extremity in patients with acute cerebrovascular accident. Issue 2 (January 2018) - Pan, Xiao-Li
Abstract : Abstract: This study aims to investigate the efficacy of early rehabilitation therapy on the movement ability of hemiplegic lower extremity in patients with acute cerebrovascular accident (CVA). A total of 86 patients who suffered from acute CVA were selected and divided into 2 groups, according to random number tables: control group, and research group. Patients in the control group received routine primary therapy, while patients in the research group received rehabilitation based on the basic therapy. The recovery of hemiplegic limb movement ability and the improvement of daily living ability before and after treatment were evaluated using the simplified Fugl–Meyer assessment (FMA), neurologic deficit scale (NDS), and Barthel index (BI). After treatment, the clinical efficacy and satisfaction degree for treatment were compared. The FMA, NDS, and BI of patients in these 2 groups were distinctly ameliorated after treatment ( P <.05). After treatment, the ameliorated degrees of FMA, NDS, and BI in the research group were obviously superior to those in the control group, and the differences were statistically significant ( P <.05). The total efficacy and satisfaction degree in the research group were evidently higher than those in the control group after early rehabilitation therapy, and the differences were statistically significant ( P <.05). Early rehabilitation therapy can significantly ameliorate the movement ability of hemiplegic lower extremity in patients with acute CVA. Its therapeutic effect is remarkable. Hence, it is worthy of popularizing in clinical practice.